Ethnomathematics Integrated Student Worksheet on Area Measurement Material Improves Elementary School Students' Creative Thinking Ability - Novelita, Nevi; Fauzan, Ahmad; Yerizon; Fitria, Yanti; Devian, Lora (International Journal of Elementary Education, 2024)
The problem in learning mathematics is the low ability to think creatively. Students are less able to produce innovative ideas to overcome new problems. This research aims to develop a valid and practical integrated ethnomathematics student worksheet. The type of research used in this research is development research. The research model used is the Plomp model, which divides the development stage into three phases: the initial investigation, development, and assessment. The subjects of this research were one mathematics material expert, 1 Indonesian language expert, and one art expert, as well as three teachers as a test of media practicality. The trial subjects for this research consisted of individual trials consisting of 3 students and small group trials consisting of 9 students. The methods used to collect data are observation, interviews, questionnaires, and tests. The instruments used to collect data were questionnaires and tests. Data analysis techniques are carried out qualitatively and quantitatively, as well as inferential statistics. The results of this research are validation results of 3.63 with a very valid category. The students' practicality results were 93.05 in the very practical category. The students' practical results were 96.04 in the very practical category. The t-test results show an influence of the Ethnomathematics Integrated Student Worksheet on Extensive Measurement Material on students' creative thinking abilities. It was concluded that the Student Worksheet integrated Ethnomathematics in data area measurement material was very valid and very practical, so it was suitable for use in learning in the fourth grade of elementary school.